Does Hearing Impairment Affect Mental Health Among Chinese Older Adults? Evidence from the Chinese Longitudinal Healthy Longevity Survey - Sun J; Li H; Jin L; Luo H (Dove Medical Press, 2021)
Jian Sun,1 Hongheng Li,2 Ling Jin,3 Hongye Luo2 1School of International and Public Affairs, Shanghai Jiao Tong University, Shanghai, People’s Republic of China; 2School of Information and Management, Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, People’s Republic of China; 3Liuzhou People’s Hospital, Liuzhou, Guangxi Zhuang Autonomous Region, People’s Republic of ChinaCorrespondence: Hongye LuoSchool of Information and Management, Guangxi Medical University, Nanning, Guangxi Zhuang Autonomous Region, 530021, People’s Republic of ChinaTel +86-139-7883-1304Email hongye283@163.comBackground and Aim: Hearing impairment is a commonly reported chronic condition among older adults. Hearing impairment is significantly associated with reduced quality of life and diminished function status. This study aimed to investigate the association between hearing impairment and mental health among Chinese older adults, with a focus on exploring the moderating effects of social participation and exercise on this association.Methods: The data of this study were obtained from the 2018 wave of Chinese Longitudinal Healthy Longevity Survey (CLHLS). We employed ordinary least squares regression models to analyze the effect of hearing impairment on mental health. Propensity score matching (PSM) and doubly robust estimation were employed to conduct robustness checks.Results: Hearing impairment produced an adverse effect on Mini-Mental State Examination (MMSE) score (coefficient = − 1.4073, p < 0.001), while it had a positive effect on depression score (coefficient = 0.8682, p < 0.001). Further analyses using PSM and doubly robust estimation reported similar results. Moreover, social participation (coefficient = 0.9424, p < 0.001) and exercise (coefficient = 0.7001, p < 0.01) moderated the association between hearing impairment and MMSE score. Social participation (coefficient = − 0.5991, p > 0.05) and exercise (coefficient = 0.7806, p > 0.05) did not moderate the association between hearing impairment and depression score.Conclusion: We provide robust evidence indicating that hearing impairment had significantly negative effects on the cognitive function and depression status of older adults. Furthermore, we find that social participation and exercise relieved the negative effect of hearing impairment on cognitive function.Keywords: hearing impairment, mental health, social participation, exercise, China